Expertise and Its Relation to Audit Decision Quality* - BÉDARD, JEAN (Contemporary Accounting Research, 1991)
Abstract. This research study examines the effect of expertise on the quality of audit decision making in an audit planning context. Unlike previous studies, expertise is measured in terms of domain‐specific knowledge. The quality of audit decision making is evaluated with three measures: consistency with professional standards, consistency with the firm's standards, and consensus among auditors. In general, findings indicate that the quality of audit decision making, as defined in this study, is better among experts than among novices. More specifically, it appears that both experts and novices possess some minimum level of knowledge to be consistent with professional standards. Second, experts are more consistent with firms' standards for both reliance and substantive decisions, indicating that expert auditors may have finer knowledge than novices. Finally, the experts' consensus level is higher than the novices' consensus level for standard auditing situations although for less standard situations, the consensus level is lower for experts.